Ambiguity and uncertainty in 'breaking bad news' simulation: Lessons from standardized patients' different personality types - Koski, Kaisu; Ostherr, Kirsten (Research and Humanities in Medical Education, 2021)
Introduction: Ambiguity and uncertainty are intrinsic aspects of contemporary medicine, and there is a need for methods to train medical students to tolerate them better. This article distinguishes the ways that different standardized patient (SP) personality types provide opportunities for medical students to practice tolerating ambiguity and uncertainty associated with breaking bad news (BBN). Methods: This ethnographic study draws data from nine student encounters with two female SPs who specialize in the BBN simulation. It utilizes the literary concepts of “unfinalizability” and parallel “time zones” to reflect upon manifestations of uncertainty and ambiguity in SP performances. Results: The SPs challenged the linear progression of the BBN encounter by including shifts between different time zones in the patient’s mental-experiential continuum. The study identified seven main forms of resistance in the SP performance, all geared toward challenging the linear and complete conduct of the student performance: resisting being considered a patient, resisting decision-making, resisting authority, resisting here-and-now, resisting being seated, resisting closure, and resisting death/life. Discussion: The SPs’ distinct personality types have the potential to improve students’ ability to respond to individuals with different temporal orientations, and support them to tolerate encounters with various kinds of open endings.